Clustering of Bigdata in Application Review Analysis - M Geetha Yadav , S Srihitha , C Tejaswi , K Srikanth (International Journal of Advanced Science and Technology, 2020)
Up to date, most of the people like on-line searching. they'll merely have a fast look on others and install apps. Over 90% customers in one hundred browse reviews before installing ,these helps them to assess that applications performs sensible and it help others to decide The project clustering of big data in application Review Analysis helps to search out a lot of facts regarding application. In this project we have a tendency to collect numerous classes of application reviews and analyze positive and negativereviews against product-wise. This helps to extend the installations of a specified app. We make use of PIG for processing data and classify reviews consequently